2014
DOI: 10.1039/c3ee43899f
|View full text |Cite
|
Sign up to set email alerts
|

Non-precious metal electrocatalysts with high activity for hydrogen oxidation reaction in alkaline electrolytes

Abstract: Polarization curves of hydrogen oxidation on a Pt disk, electroplated Ni and CoNiMo multimetallic layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
306
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 341 publications
(335 citation statements)
references
References 36 publications
10
306
0
Order By: Relevance
“…To further improve the catalytic activity, Yan and co-authors [98] electrochemically deposited NiCoMo on Au substrates. They showed that the optimal composition of Co 0.12 Ni 5.1 Mo produced a high exchange current density of 0.015 mA cm −2 .…”
Section: Science China Materialsmentioning
confidence: 99%
“…To further improve the catalytic activity, Yan and co-authors [98] electrochemically deposited NiCoMo on Au substrates. They showed that the optimal composition of Co 0.12 Ni 5.1 Mo produced a high exchange current density of 0.015 mA cm −2 .…”
Section: Science China Materialsmentioning
confidence: 99%
“…4 On the other hand, AMFCs allow the use of non PGMs catalysts in the less aggressive medium (alkaline, pH = 13) where most of the transition metals form stable solid species. 5 Therefore, the combination of a very low content of active PGM with a low-cost transition metal is very appealing as HOR catalyst in AMFCs. As a typical example, the use of a low amount of Pd, which is a relatively abundant PGM, in combination with abundant transition metals like Ni is very attractive for HOR in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, recent studies have shown that the HOR/HER rates of noble metal electrodes in the alkaline environment are much slower than in acidic electrolytes by about two orders of magnitude, 18,19 but still remain a few order of magnitude higher than the latest noble metal free HOR catalyst systems. [20][21][22] Even if the reasons for this activity decrease on noble metal electrodes remain not yet fully understood, these studies have highlighted the lack of fundamental understanding * Electrochemical Society Student Member.…”
mentioning
confidence: 99%